2016
DOI: 10.1002/slct.201601301
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Determination by Luminescent Chemo–enzymatics

Abstract: A novel methodology for the determination of the number‐average molecular weight (Mw) of linear, branched and crosslinked polymers is disclosed. The method relies on chemo‐enzymatic‐triggered fluorescence of dormant CdTe polymer‐caged quantum dots synthesised in supercritical carbon dioxide. Polyurea (PURE) dendrimers (G1, G4, G5 and G6) are presented as a case study using the enzyme urease but the protocol is applicable to other synthetic and natural polymers. Simple, versatile and accurate, luminescent chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…19 In recent years, we developed a new class of fluorescent, biocompatible and water-soluble amine-terminated PURE dendrimers 20 whose synthesis follows a green methodology that allows low-cost gram scale preparation of dendrimers of high generations. 21 We also demonstrated that core-shell nanoparticles (PURE G4 OOx 48 ) may be prepared by surface functionalization of PURE dendrimers with biocompatible oligo-oxazolines (POxylation). 22 This work inspired us to perform the hydrolysis of the POxylated dendrimers (PURE G4 OOx 48 ), more precisely its OOx surface layer, to the corresponding highly cationic core-shell dendrimers and explore their antimicrobial and antifungal potential.…”
Section: Synthesis and Characterization Of Pure Pharmadendrimersmentioning
confidence: 85%
“…19 In recent years, we developed a new class of fluorescent, biocompatible and water-soluble amine-terminated PURE dendrimers 20 whose synthesis follows a green methodology that allows low-cost gram scale preparation of dendrimers of high generations. 21 We also demonstrated that core-shell nanoparticles (PURE G4 OOx 48 ) may be prepared by surface functionalization of PURE dendrimers with biocompatible oligo-oxazolines (POxylation). 22 This work inspired us to perform the hydrolysis of the POxylated dendrimers (PURE G4 OOx 48 ), more precisely its OOx surface layer, to the corresponding highly cationic core-shell dendrimers and explore their antimicrobial and antifungal potential.…”
Section: Synthesis and Characterization Of Pure Pharmadendrimersmentioning
confidence: 85%
“…However, due to the stability of the reagents and derivatives at lower pHs, the method is also applicable in studies involving tumor cells or tissues under acidic environments [13]. PURE dendrimers were chosen as a model drug delivery system due to their reported biocompatibility and biodegradability [14]. It is well known that PURE dendrimers in aqueous solutions have the ability to produce positively charged species [15] as a result of amines protonation.…”
Section: Resultsmentioning
confidence: 99%
“…Cell Cytotoxicity Assay. Cells were treated with nanogalactose and nano-HTPB 14 of varying concentrations (5,10,15,20,50, or 200 nM) for 48 h. Proliferation of cells was determined by standard 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) analytic protocol, as previously described. 82 Analysis of Cell Cycle Distribution.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Semiconducting, fluorescent quantum dots (QDs) have attracted significant attention in biological and biomedical applications , such as cellular imaging, drug delivery, and bio sensing. Their distinguished optical attributes, including high quantum yield, size-dependent tunable emission, superior brightness, and photostability, make them appealing as fluorescent probes for bioimaging. Coating hydrophobic QDs with hydrophilic organic surfactants is a general strategy for making them water-soluble and biocompatible. , Biomolecules such as DNAs, proteins, and small biomolecules can be appended to QD to target cellular receptors. It can be achieved by cross-linking chemistry, biotin–avidin interactions, , or ligand exchange methods .…”
Section: Introductionmentioning
confidence: 99%